Answer:
(6x-2) - (-x+5)
= 6x-2 +x -5
= 7x -7
if you're trying to solve for x, then look below
7x=7
x=1
Answer:
56
Step-by-step explanation:
z varies jointly with x and y:
z = kxy
When x = 2 and y = 2, z = 7.
7 = k(2)(2)
k = 7/4
z = 7/4 xy
When x = 4 and y = 8:
z = 7/4 (4)(8)
z = 56
You follow the rules for the quadratic formula, where
x= (-b +- √(b²-4ac) )/2a
Filling a, b and c in yields
x = (8 +- √(64-164) ) / 2 =>
x = (8 - √-100)/2 or x = (4 + √-100)/2
Well, √-100 = 10i, so then you simplify to the last answer, D:
x = 4-5i or x=4+5i
Answer:
5 4 3 2 1 0 -1 -2 -3 -4 -5
Step-by-step explanation: